ANALYSIS AND EXPERIMENTAL WORK ON COMPRESSIVE STRENGTH OF CONCRETE CUBE USING STEEL CRIMPED FIBER - sudhakar, P.; Nizar, N.Mohamed (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
SFC is a composite material made of cements, water, fine and coarse aggregate, and a dispersion of discontinuous, small fibers. These short discrete fibers are uniformly distributed and randomly oriented. They are mixed with concrete before pouring. It is well known that plain concrete is brittle and weak under flexural loads. To eliminate the disadvantages of plain concrete is added fibers into concrete mix. All admixtures meeting ASTM specifications for use in concrete are suitable for use in SFC. Steel fiber concrete (SFC) has gained increased popularity in construction industries in recent years.